VOCABULARY JOURNAL: A VOYAGE TO SUCCESSFUL WRITING PERFORMANCE - Ting Pick Dew, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The importance of vocabulary competency has been long established as it serves as a crucial element in learning English as a second language. It is however more prominent in writing as the breadth and depth of students’ vocabulary are reflected in the general quality of their writing. By utilising Stufflebeam’s (2003) Product Evaluation model, this paper reports the impacts of the study on keeping vocabulary journal towards 71 students’ writing performance at one of the secondary schools in Sabah. It evaluated their attitudes towards keeping vocabulary journal, identified positive, negative, intended and unintended outcomes of keeping vocabulary journal and aimed to find out whether there is any difference in the students’ writing scores prior to and after keeping vocabulary journal. A mixed-method was employed into the study. Self-reported survey and class discussion were employed in the qualitative approach, whereas the quantitative part of this study involved only the writing scores from the results of pre-test and post-test. The results indicated positive students’ attitudes towards vocabulary journal. It also highlighted four outcomes of the study; positive and negative outcomes, as well as intended and unintended outcomes. Although the pre-test and post-test writing scores were insignificant enough to make any difference, the introduction of vocabulary journal into writing classroom has surely made an impact on the students. This study added empirical support onto the claims on the benefits of vocabulary journals.